Post Rally for Lloyd Bentsen for Vice President - Watkins, Howard::::::::: (1988)
Diego Arambula, Miguel Arambula, Joaquin Arambula, Juan Arambula, Carmen Arambula, March Fong Eu and Adam Watkins in background